Current situation and effectiveness of palliative care training for staff in an emergency care medical consortium hospital: a cross-sectional study - Zong, Liang; Jiang, Hui; Zhu, Huadong; Liu, Jihai; Xu, Jun; Ning, Xiaohong; Li, Fan; Gao, Jian; Li, Bo; Shi, Di; Rao, Xin (Frontiers in Medicine, 2025)
BackgroundThe emergency department (ED), usually deemed not the most frequent setting for palliative care (PC), has increasingly been mentioned for its potential critical role in end-of-life patient care. However, how the training affects PC performance remains to be investigated. This study aims to investigate the current PC standard of care and effectiveness of PC training in a Chinese emergency care medical consortium hospital.MethodsWe conducted an anonymous online census targeting the emergency care providers in the consortium hospital. The questionnaire included respondents’ demographics, PC knowledge, PC practice, and whether they have received any PC training. Outcome variables included: confidence in clinical implementation, perceptions about death, and attitudes toward PC implementation with Likert five score rating. Factors associated with better PC knowledge and performance were identified by analysis of the association between rating scores and participant characteristics.Results923 staff participated in the study, while 429 (46.5%) received PC training. Training participation was significantly associated with age, education, occupation, rank, working years, and experience of family members’ death (p < 0.05). Training improved the total score of knowledge and practice of PC (median 90 vs. 100, p < 0.001), the confidence in clinical PC management (confidence score: 36 vs. 40, p < 0.001), and attitudes toward PC implementation (attitude score: 37 vs. 40, p = 0.048). Offline lecture-based learning was the primary training form in this hospital. The ORs of case-based learning, online lecture video, and community training project to higher total scores were 1.94 (95% CI 1.18–3.17, p = 0.009), 2.09 (1.23–3.56, p = 0.006) and 0.17 (0.04–0.63, p = 0.008), respectively. Meanwhile, cased-based learning, online lecture video, and community training project contributed significantly to the confidence score. So did the lecture offline to the score of perception about death (perception score). The OR of meeting online to attitude score was 1.69 (1.05–2.73, p = 0.030).ConclusionPalliative care training is associated with better self-rating of PC among ED care providers. However, there is a significant gap for improvement, particularly for the community training programs.